Effects of Mindfulness-Based Interventions on Salivary Cortisol in Healthy Adults: A Meta-Analytical Review - Sanada, Kenji; Montero-Marin, Jesus; Alda Díez, Marta; Salas-Valero, Montserrat; Pérez-Yus, María C.; Morillo, Héctor; Demarzo, Marcelo M. P.; García-Toro, Mauro; García-Campayo, Javier (Frontiers in Physiology, 2016)
Objective. The aim of the present study was to elucidate the effects of Mindfulness-based interventions (MBIs) on salivary cortisol levels in healthy adult populations. Method. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs), published between January 1980 and June 2015 in PubMed, EMBASE, PsycINFO and the Cochrane library. The PRISMA and Cochrane guidelines were followed. The pooled effect sizes were calculated with the random-effects model, using Hedges’ g values, and heterogeneity was measured using the I2 statistic. The contribution of different characteristics of participants and programmes were assessed by meta-regression models, using beta coefficients. Results. Five RCTs with 190 participants in total were included in this systematic review. The overall effect size (ES) for improving the state of health related to cortisol levels was moderately low (g=0.41; p=0.025), although moderate heterogeneity was found (I2=55; p=0.063). There were no significant differences between active (g=0.33; p=0.202) and passive (g=0.48; p=0.279) controls, but significant differences were found when comparing standard (g=0.81; p=0.002) and raw (g=0.03; p=0.896) measures. The percentage of women in each study was not related to ES. Nevertheless, age (beta=-0.03; p=0.039), the number of sessions (beta=0.33; p=0.007) and the total hours of the MBI (beta=0.06; p=0.005) were significantly related to ES, explaining heterogeneity (R2=1.00). Conclusions. Despite the scarce number of studies, our results suggest that MBIs might have some beneficial effect on cortisol secretion in healthy adult subjects. However, there is a need for further RCTs implemented in accordance with standard programmes and measurements of salivary cortisol under rigorous strategies in healthy adult populations.